Treatment Failure of Ampicillin to Children with Pneumonia at Dr. Hasan Sadikin General Hospital Bandung from 2014â2015 - Suharno, Kania Devi; Husen, Ike Rostikawati; Sudarwati, Sri (Althea Medical Journal, 2017)
Background: Pneumonia is one of the causes of death in infants in developing countries especially Indonesia. Appropriate treatment is needed to decrease mortality rate in children due to pneumonia. Ampicillin is one of first choices empirical antibiotic to children with severe pneumonia. The study was aimed to determine the failure rate of ampicillin in children with severe pneumonia.Methods: This study was a descriptive study which used medical records as source of data. Subjects were children aged 2â59 months with World Health Organization (WHO) defined with severe pneumonia and treated with intravenous ampicillin during January 2014 to July 2015 at Dr. Hasan Sadikin General Hospital Bandung. Samples were obtained using total sampling method while variables were analyzed using statistics software.Results: This study acquired 107 patients who met the inclusion criteria with 23.36% of them aged 2â11 months and 62.21% aged 12â23 months. Majority of subjects were male amounted as 63.55% while female occupied 36.45%. Treatment failure on the third day was 45.8% while 16.7% on the sixth day of therapy with majority failure due to existence of lower chest indrawing.Conclusions: Treatment failure on the third and sixth day of therapy still high that is characterized by the existence of lower chest indrawing as its main factor. [AMJ.2017;4(1):100â6]DOI:Â 10.15850/amj.v4n1.1029